Isolation improvement of dual feed patch antenna by assimilating metasurface ground - Ullah, M.H.; Ahsan, M.R.; Mahadi, W.N.L.W.; Latef, T.A.; Uddin, M.J. (Microwave and Optical Technology Letters, 2015)
A new octagonal ring shape metasurface structure (MSS) has been design and implemented at the back of a dual feed planar printed Ultrawideband array antenna. The proposed MSS incorporated antenna has been design and fabricated on a high permittivity (epsilon(r)=15) ceramic filled biopolymer-based sandwich structured dielectric substrate. A significant improvement of isolation (S-21) between dual port array elements of the proposed antenna has been achieved by assimilating 6 x 9 octagonal ring shape MSS with near zero refractive index in the ground plane. Measurement result shows that the proposed antenna with MSS loading has been achieved the reflection coefficient (S-11<-10 dB) bandwidths of 1.3, 1.02, 0.75, and 1.8 GHz. Stable radiation patterns with the gains of 3.42, 4.14, 5.46, and 8.28 dBi have been measured at the resonant frequencies 3.1, 4.41, 6.2, and 8.75 GHz. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1406-1409, 2015